PERAN BRAND IMAGE SEBAGAI MEDIATOR ANTARA COUNTRY OF ORIGIN DENGAN PURCHASE INTENTION - Kusuma, Ida Bgs Hendra Prawira; Giantari, I Gusti Ayu Ketut (E-Jurnal Manajemen; Vol 7 No 8 (2018)DO - 10.24843/EJMUNUD.2018.v07.i08.p11, 2018)
This research aims to clarify the role of the brand image in the mediated relationship of country of origin with the purchase intention . Research conducted in the city of Denpasar with number of samples as much as 120 respondents who have never bought a car Engine products. The sample was determined using a model of non-probability sampling, with the technique of purposive sampling. Data analysis technique used is a path analysis and test sobel. The results showed that the hypothesis is accepted. Country of origin effect positively and significantly to the brand image, country of origin effect positively and significantly to purchase intention, brand image and positive effect significantly to purchase intention, brand image mediate the influence of country of origin against the purchase intention. The company's expected future make use of country of origin of the company namely Isuzu Japan for means of promoting products to Isuzu cars make consumers believe the company's offer on the product so that it can have an impact on the incidence of purchase intention.   Keywords: country of origin , brand image, purchase intention